Trifluoromethyl and benzyl ether side groups containing novel sulfonated co-poly(ether imide)s: Application in microbial fuel cell - Kumar, Anaparthi Ganesh; Saha, Sayantani; Komber, Hartmut; Tiwari, Bikash Ranjan; Ghangrekar, Makarand M.; Voit, Brigitte; Banerjee, Susanta (European Polymer Journal, 2019)
A new diamine monomer namely 4,4′-((2′,5′-bis(benzyloxy)-3,3′'-bis(trifluoromethyl)-[1,1′:4,4′'-terphenyl]-4,4′'-diyl)bis(oxy))dianiline (TADBE) was prepared. A series of sulfonated co-poly(ether imide)s was synthesized using this diamine as one of the co-monomers along with 4,4′-diaminostilbene-2,2′-disulfonic acid (DSDSA) on reaction with a six-membered dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride (NTDA). The degree of sulfonation (DS, 60-90) of the copolymers was controlled by varying the feed ratio of TADBE/DSDSA and the obtained copolymers were designated as DBN-XX (XX = 60, 70, 80 and 90, which signifies the DSDSA feed percentage). The copolymer structures and compositions were confirmed by NMR and FTIR analysis. Membranes were prepared through solution casting route using dimethyl sulfoxide as solvent followed by high-temperature annealing. The membranes showed high thermal (e.g., DBN-60, Td10 ∼327 °C) and mechanical stabilities (e.g., DBN-60, tensile strength ∼94 MPa), good hydrolytic stability (e.g., DBN-60, >99 retain wt%) and low water uptake (e.g., DBN-60, ∼17 wt% at 80 °C). Polymer composites were prepared by loading different weight percentages of cerium oxide (2.5, 5 and 7.5 wt%, respectively) to enhance the peroxide stability of the copolymer DBN-90 with high DS value. TEM and AFM studies of the pristine membranes confirmed a well phase separated morphology and this was further supported from SAXS profiles. The proton conductivity (e.g., DBN-90, ∼244 mS cm−1) and microbial fuel cell performance (e.g., DBN-90, power density ∼576 mW m−2) of the membranes were comparable to Nafion® 117 (power density ∼563 mW m−2) under similar experimental conditions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Mechanical properties; Microbial fuel cell; Peroxide radical resistance; Proton exchange membrane; Sulfonated polyimide